A new species of Neominois from northeastern Mexico (Lepidoptera: Nymphalidae: Satyrinae) - Warren, Andrew D.; Austin, George T.; Llorente-Bousquets, Jorge E.; Luis-Martínez, Armando; Vargas-Fernández, Isabel (Zootaxa, 2008)
A new species from northeastern Mexico, Neominois carmen (Lepidoptera: Nymphalidae: Satyrinae), is described, illustrated, and compared with its only known congener, N. ridingsii. The species is distinguished from the latter by its orange coloration and shape of and pattern on the wings as well as by differences in the genitalia of both sexes.